Pengaruh Persepsi Siswa Tentang Metode Diskusi Dan Pemanfaatan Media Pembelajaran Terhadap Keaktifan Belajar Mata Pelajaran Ekonomi Pada Siswa Kelas XI IPS SMA Negeri 2 Wonogiri Tahun Ajaran 2015/2016 - Khadafi, Mochammad Agia, Drs. Djumali, M.Pd (2016)
The active participation is a factor that can affect student achievement. The role of liveliness no doubt in learning. Energy change in the form of a person's physical activity. This research was conducted in SMA Negeri 2 Wonogiri with the aim of research to determine the effect of the method of discussion and utilization of instructional media to learn activeness class XI IPS SMA Negeri 2 Wonogiri individually and together. The method used: the type of research with quantitative methods associative way. The study used a survey design because it does not take all members of the population sampled. The study population was all students of class XI IPS SMA Negeri 2 Wonogiri which numbered 120 students with a sample of 89. The sampling technique using Simple Random Sampling lottery. The analytical tool used Mechanical Testing Instrument (Validity and reliability test), Test Prerequisites Analysis (Normality Test, Test and Test Linearity multicolinearity). Data Analysis Techniques used: 1. Regression Analysis, Test In Unison (Test F), 2) Significance in Partial / T test. Results of the analysis: 1) The results of multiple linear regression coefficient of 0.550 Method Discussion, Utilization Learning Media for 0,494, demonstrating that variable Method Discussion and Utilization Learning Media has an effect on students' learning activeness. 2) The results obtained t t test for variables Method Discussion of 7.299 while ttable 1,988, then Ho is rejected so that there is significant influence between activeness Learning Method Discussion of the individual. and 3) From the results obtained t t test for variables Instructional Media Utilization of 6.982 while ttable 1,988, then Ho is rejected so that there is significant influence between the liveliness Instructional Media Utilization Learning individually. 4) The results obtained F-test analysis of F = 70.918> F table = 3.103, then Ho is rejected so that together there is a significant effect Method Discussion (X1), Utilization Learning Media (X2) on the students' learning activeness.